Effect of Papaya Leaves in Feed on the Immunity of Silver and Gold Arab Laying-Hens - Sjofjan, Osfar; Nurgiartiningsih, V.M. Ani; Suyadi (International Journal of Poultry Science, 2016)
The immunity of Arab Laying-hens is the key to success in the eggs production. The study aims to determine the effect of the level of papaya leaves (Carica papaya L.) in the feed to the immunity on Arab Laying-hens with different feather colors (Silver and Gold). The experimental design was completely randomized in a factorial arrangement (feather colors X level of papaya leaves). Immunity was determined by the number of CD4, CD8 and B220 after 60 days treatment. The results showed the feather colors and interaction of feather colors and the level of papaya leaves had no significant (p>0.05) effect toward CD4, CD8 and B220. However the number of B220 tended to increase by increasing the level of papaya leaves in feed in both of Silver and Gold Arab Laying-hens. In conclusion, the immunity expressed by CD4, CD8 and B220 was similar in both Silver and Gold Arab Laying-hens, as will go for the level of papaya leaves in feed.